Pelaksanaan Pendidikan Karakter Religius melalui Program Sekolah Kelas Tahfidz Al-Qur’an di SD Negeri 3 Sungai Ulin - Jumainah, Hj.; Enggar Wibowo, Dodiet; Makhtuna, Wulida (Arfah BHMS Foundation, 2025)
This study aims to (1) describe and explain the implementation of religious character education through the Tahfidz Al-Qur’an class program at SD Negeri 3 Sungai Ulin in terms of planning, implementation, and evaluation; and (2) identify the supporting and inhibiting factors in the implementation of the program. This research employed a qualitative case study approach. The research subjects included the school principal, Tahfidz teachers, and students. Data collection techniques involved interviews, observations, and documentation. Data were analyzed using the Miles and Huberman model. The findings revealed that religious character education was integrated into the curriculum through a well-structured planning process, effective teaching strategies, and continuous evaluation based on religious character indicators. Supporting factors included school leadership commitment and parental involvement, while inhibiting factors involved limited instructional time and infrastructure constraints.